(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
Epilepsy is a chronic neurological disorder characterized by recurrent epileptic seizures resulting from abnormal, excessive neuronal activity in the brain. This article reviews the etiology, clinical types, diagnosis, and modern treatment strategies of epilepsy. The content is based on international scientific literature and recent research findings.